Recycled art from plastic waste for environmental sustainability and aesthetics in Ghana - Asamoah, Samuel Prophask; Adom, Dickson; Kquofi, Steve; Nyadu-Addo, Ralph (Research Journal in Advanced Humanities, 2022)
The study rooted in the eco-innovation theory aimed at investigating the effects of plastic waste in the Kokrobite and Bortianor communities in Accra while finding proactive ways of using recycled art from plastic waste, with post-use packages in focus to sensitize community members on the negative effects of plastic waste. Phenomenology and art studio-based research designs under the qualitative approach were adopted for the study. The study was carried out from August 2021 to July 2022. Personal interviews and focus group discussions with 72 snowball and purposively sampled study participants. The data from the study were analysed using the Interpretative Phenomenological Analysis. The study revealed that the improper management of post-used plastic items in the study areas was a major factor that contributed to environmental pollution. An artistic installation was executed using plastic waste. Visually, it enhanced the environmental aesthetics in the community while philosophically serving as a sensitization tool on the effects of plastic waste. In the quest for a solution to plastic pollution, innovation from post-used plastic items is the ultimate answer. The Ministry of Education and Ghana Education Service in collaboration with the Ministry of Environment Science Technology and Innovation and the Ministry of Tourism Arts and Culture can organize such competitions to reward students of all levels who create innovative products from plastic waste.